Integrated Energy System Planning Based on Life Cycle and Emergy Theory - Wang, Jun; Du, Wei; Yang, Dongmei (Frontiers in Energy Research, 2021)
Integrated energy system (IES) is of great significance in the construction of the modern energy system. Reasonable planning is one of the important means to improve the economy of the IES and promote the consumption of renewable energy. However, the complex coupling characteristics between energy sources make it difficult to quantify the production efficiency of multi-energy heterogeneous resources uniformly in the economic benefit model during the planning cycle. Quantifying the production efficiency of the IES for planning is currently an urgent problem to be solved. This study proposes a planning method for the IES based on the life cycle and emergy theory. First, emergy theory is applied to quantify the production efficiency of the IES. A complete economic benefit model is established based on life cycle theory. Second, a bi-level planning model of the IES is established. The upper-level model aims at minimizing the whole life cycle cost of the IES to plan the capacity and location of the coupling equipment. The lower-level model aims at maximizing the emergy yield ratio of the IES to provide the operating data for the upper level. Finally, comparing experimental evaluations with traditional planning schemes considering annual average cost and energy quality coefficient, the method in this study reduces planning costs by 23.16% and increases the consumption rate of renewable energy by 4.26%. It can be seen that the planning method proposed in this study improves the planning economy and the level of renewable energy consumption of the IES.